2015
DOI: 10.1177/1391561415598458
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Foreign Direct Investment in Sri Lanka

Abstract: Foreign direct investment (FDI) can play a significant role in achieving rapid economic growth in developing countries such as Sri Lanka. Even after the 30-year-long war that ended in 2009, the economy is still struggling to convince domestic and foreign investors that Sri Lanka is ‘ready for business’. In the light of this situation, identifying the factors that could influence FDI inflows into Sri Lanka is crucial to design policies aimed at attracting more FDI. This article empirically investigates the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…Trade openness also shows positive and statistically significant impact on inward FDI long-run. Finally, the study suggested giving more consideration on GDP, exchange rates, interest rates, and the level of external trade to attract FDI inflows in Sri Lanka, in line with Ravinthirakumaran et al (2015). Uduak et al (2014) examined the determinants of foreign direct investment in Brazil, Russia, India, China, and South Africa (BRICS) and Mexico, Indonesia, Nigeria, and Turkey (MINT) using pooled time-series cross sectional analysis and random effect model over the period 2001-2011.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Trade openness also shows positive and statistically significant impact on inward FDI long-run. Finally, the study suggested giving more consideration on GDP, exchange rates, interest rates, and the level of external trade to attract FDI inflows in Sri Lanka, in line with Ravinthirakumaran et al (2015). Uduak et al (2014) examined the determinants of foreign direct investment in Brazil, Russia, India, China, and South Africa (BRICS) and Mexico, Indonesia, Nigeria, and Turkey (MINT) using pooled time-series cross sectional analysis and random effect model over the period 2001-2011.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Hence, the break period is defined as: TB 1982 ≤ p ≤ 2010 = 1. Besides the civil war which includes the Eelam Wars that continued even after the ceasefire agreement in 2002, and the violence that ended with a defeat of the Tamil Tigers in 2009 (Ravinthirakumaran, Selvanathan, Selvanathan, & Singh, 2015), other events include the extreme tsunami in 2004 (Becchetti & Castriota, 2010), and the 2007/2008 global financial crisis. The latter affected the real and services sector including tourism and induced knock-on effects on the overall economy (Hemachandra, 2011).…”
Section: Breaks In Seriesmentioning
confidence: 99%
“…The structural stability of the coefficients was analyzed using the cumulative sum (CUSUM) and the cumulative sum square (CUSUMQ) tests as they are a useful diagnostic tools for parameter constancy (Ravinthirakumaran, Selvanathan, Selvanathan, and Singh, 2015). As such, both tests are based on recursive residuals and have an advantage over other tests, as it does not require prior knowledge of the structural break point (Turner, 2010).…”
Section: Cusum and Cusmq Testsmentioning
confidence: 99%